Dynamic gas supply mechanism and theoretical production modes of free gas-rich deep coal reservoirs - Shida CHEN; Taiyuan ZHANG; Dazhen TANG; Hao XU; Shu TAO; Song LI; Shuling TANG (Meitian dizhi yu kantan)
Objective and Methods The production processes of adsorbed and free gases and the dynamic partitioning mechanism behind the production efficiency of both gas types are critical scientific issues to be addressed urgently in the exploration and production of deep coalbed methane (CBM). Based on the test and assay data of cores from exploration wells, this study systematically analyzed the theoretical production of deep CBM resources. By integrating the building of mathematical and numerical models, carbon isotope monitoring of methane, and the analysis of production curves, this study revealed the spatiotemporal evolutionary processes of production-induced pressure drop expansion, adsorbed gas desorption, and free gas seepage, as well as their production effects. Finally, this study determined the synergistic gas supply mechanism and theoretical production modes of methane with multiple occurrence states in free gas-rich deep coal reservoirs.Results and Conclusions During the production of a deep CBM well, free and adsorbed gases exhibited a continuous, synergistic gas supply characteristic and a partitioning relationship characterized by competitive production, with the produced gas identified as a mixture of both gas types at any given time. The dynamic partitioning ratios of methane with varying occurrence states depended on the superposition of free gas mass transfer efficiency and adsorbed gas desorption efficiency within the pressure propagation domain in varying production stages, with the efficiencies centering on pressure drop-induced desorption and differential pressure-driven seepage. Deep coal reservoirs would experience an entire desorption process, with substantial pressure drop required to reach critical desorption nodes. It is challenging to resolve the inherent contradiction between the high reservoir pressure and low desorption efficiency in the early stage and the high desorption efficiency and limited pressure drop in the late stage. The pressure drop funnel, adsorbed gas exhibited a relatively low average desorption rate, with gas supply units concentrated primarily in high-permeability stimulated zones. Free gas showed a continuously expanding supply radius and a consistently high production proportion. High-density well group co-production or the heterogeneity of gas-water distribution can lead to adjustments in the adsorbed and free gas proportion, and the adjustment process depend on the dynamic matching relationship between gas supply unit expansion and fluid supply capacity. Free and adsorbed gases demonstrated the production characteristics of sharp increase - gentle decline (or sharp increase - sharp decline - gentle decline) and gentle increase - stability - gentle decline, respectively. Their overall production capacity can be divided into three stages primarily: rapid addition, relative stability, and slow decline. The morphologies of production curves were influenced by free gas volume, in-situ permeability, reservoir stimulation performance, and pressure drop system. For some wells, the relatively stable production stage can be further divided into two substages: sharp production decline followed by stable production. The core strategies for production growth include increasing the stimulated reservoir volume, extending the horizontal sections of wells, and pinpointing free gas-rich zones with high porosity and permeability. Meanwhile, the key to an increase in the exploration depths of deep CBM is to explore technologies for enhancing both the desorption efficiency of adsorbed gas and the overall influential depth of pressure drop. Constructing a “dynamic regulation system for drainage and production” that balances gas well lifecycle and fluid production efficiency forms the critical foundation for fully releasing production potential. Furthermore, the first priority for commercial production capacity construction of deep CBM is determining rational production capacity targets and required well-controlled areas for varying deep geological units and synergistically optimizing well completion methods, well pattern density, fracturing parameters, production allocation rates, and production cycles under the guidance of geological and engineering integration.